Investigations on the Nature of Hemophilia A - Mammen, Eberhard (Thrombosis and Haemostasis, 1963)
In this paper an inhibitor is described that is found in hemophilic plasma and serum different from any till now described inhibitor. The inhibitor only inhibits prothrombin activation in the “intrinsic clotting systems”. This inhibitor is probably not present in normal human plasma or serum. It is destroyed by ether and freeze drying, is labile to acid and storage at room temperature. It is stable upon dialysis and has not been adsorbed on barium sulfate, aluminum hydroxide or kaolin. It precipitates at 50% v/v saturation with alcohol. The nature of this inhibitor seems to be a protein or lipoprotein.Factor VIII was isolated from hemophilic plasma. The amount isolated was the same as from normal plasma and the activity properties were not different. Hemophiliacs have normal amounts of factor VIII.